C9 SUBCUTANEOUS IMPLANTABLE CARDIOVERTER DEFIBRILLATOR IN PATIENTS WITH LOW BMI: REAL–WORLD DATA FROM A EUROPEAN MULTICENTER ANALYSIS. (18th May 2022) - Schiavone, M; Gasperetti, A; Vogler, J; Mitacchione, G; Gulletta, S; Palmisano, P; Breitenstein, A; Laredo, M; Compagnucci, P; Angeletti, A; Kaiser, L; Hakmi, S; et al.
Abstract: Background: One of the current limitations of the S–ICD is the relatively large size of the generator compared to the TV (transvenous) ICD. There is little evidence whether the size of the current S–ICD generator is associated with an elevated risk of device–related complications in patients with a low body mass index (BMI). Purpose: Aim of this study was to compare the device–related complications and long–term outcomes in a large real world cohort of S–ICD recipients in patients with a BMI <18 kg/m2 compared to patients with a BMI >18 kg/m2. Methods: All consecutive patients meeting current guideline indications for ICD implantation and undergoing implantation of a S–ICD device (Boston Scientific, Marlborough, Massachusetts, USA) at 21 European institutions enrolled in the extended ELISIR registry were used for the current analysis. Patients were classified into two cohorts, depending on the BMI at the time of device implantations: BMI < 18 kg/m2 versus > 18 kg/m2. Results: Out of a total of 1497 pts, 58 pts (3.9%) had a BMI < 18 kg/m2. Patients with BMI <18 kg/m2 were younger (44.6±2.4 vs 50.8±0.4; p = 0.004) and more frequently female (58.6% vs 22.3%, p < 0.001). No differences in any of the other baseline characteristic were observed. Implantation techniques resulted comparable between the groups (rates of 2–incision technique: 87.8% vs 91.9%; p = 0.256; inter–muscular placement: 89.7% vs 83.3%; p = 0.198). Of note, the mean PRAETORIAN score at implantation of patients with BMI <18 kg/m2 was significantly lower (33.8±9.1 vs 54.1±47.3; p = 0.035), although the vast majority of patients in both cohorts qualified as at low risk of conversion failure (100% vs 91.4%; p = 0.436). Over a median follow up time of 22.4 [11.6–36.8] months, both overall device–related complications (5.2% vs 7.4%) and rates of inappropriate shocks (12.0% vs 8.8%) resulted comparable between the two groups (p = 0.517 and p = 0.385, respectively). Figure 1 reports Kaplan–Meier curves showing the combined incidence of device–related complications and inappropriate shocks in the two groups (log–rank p = 0.576). Conclusion: No differences in device–related complications and long–term outcomes after S–ICD implantation were observed in patients with BMI <18 kg/m2 compared to the remaining recipients in a large multicentered real–world analysis.